EFEKTIVITAS LAYANAN INFORMASI MENGGUNAKAN PERMAINAN UNTUK MENINGKATKAN SELF REGULATED LEARNING - Utami, Rismar Julia (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
This research background is lack of student self regulated learning, it has negative effects forthe quality and quantity of learning. Guidance and counseling services have a duty and role inimproving students self regulated learning, one of them is information service. Students will begiven an understanding and knowledge to improve student self-regulated learning byinformation service.The research purpose to reveal the effectiveness of information services toimprove student self-regulated learning. This research using quantitative research methodwith quasi-experimental approach by using the non equivalent control group design. Theresearch population was 115 students XI class in SMA N 13 Kerinci and selected by purposivesampling technique. Student self regulated learning data was Likert Scale, then analyzed usingthe Wilcoxon Signed Ranks Test and Kolmogorov Smirnov 2 Independent Samples with SPSSversion 20.00. Based on this result, guidance and counseling techers are suggested to do theinformation service planned by using the game to improve student self regulated learning.Keywords: Self regulated learning, Information Services